Local and Regional Indian Summer Monsoon Precipitation Dynamics During Termination II and the Last Interglacial. Issue 21 (14th November 2019) - Magiera, Matthias; Lechleitner, Franziska A.; Erhardt, Andrea M.; Hartland, Adam; Kwiecien, Ola; Cheng, Hai; Bradbury, Harold J.; Turchyn, Alexandra V.; Riechelmann, Sylvia; Edwards, Lawrence; Breitenbach, Sebastian F. M.
Abstract: To date Indian summer monsoon (ISM) dynamics have been assessed by changes in stalagmite δ 18 O. However, stalagmite δ 18 O is influenced by multiple environmental factors (e.g., atmospheric moisture transport, rainfall amount at the study site, and ISM seasonality), precluding simple and clear reconstructions of rainfall amount or variability. This study aims to disentangle these environmental factors by combining δ 18 O, δ 44 Ca, and elemental data from a stalagmite covering Termination II and the last interglacial from Mawmluh Cave, NE India, to produce a semiquantitative reconstruction of past ISM rainfall. We interpret δ 18 O as a mixed signal of rainfall source dynamics and rainfall amount and coupled δ 44 Ca and X/Ca ratios as indicators of local infiltration rate and prior calcite precipitation in the karst zone. The wettest conditions in our studied interval (135 and 100 kyrs BP; BP = before present, with the present being 1950 CE) occurred during Marine Isotope Stage 5e. Our multiproxy data set suggests a likely change in seasonal distribution of Marine Isotope Stage 5e rainfall compared to the Holocene; the wet season was longer with higher‐than‐modern dry season rainfall. Using the last interglacial as an analogue for future anthropogenic warming, our data suggest a more erratic ISM behavior in a warmer world. Key Points: This study represents a first multiproxy stalagmite record from the Indian summer monsoon domain covering Termination II and Marine Isotope Stage 5e Combining δ 18 O, δ 44 Ca, and elemental data helps to discriminate between rainfall source and amount and local infiltration The rainy season during Marine Isotope Stage 5e was wetter, likely with more extreme rainfall events, compared to the Holocene